Intention and Responsibility in Double Effect Cases - Chan, David K. (2000)
I argue that the moral distinction in double effect cases rests on a difference not in intention as traditionally stated in the Doctrine of Double Effect (DDE), but in desire. The traditional DDE has difficulty ensuring that an agent intends the bad effect just in those cases where what he does is morally objectionable. I show firstly that the mental state of a rational agent who is certain that a side-effect will occur satisfies Bratman's criteria for intending that effect. I then clarify the nature of the moral distinction in double effect cases and how it can be used to evaluate the moral blameworthiness of agents rather than the moral status of acts. The agent's blameworthiness is reduced not by his lack of intention but by his desire not to bring about the side-effect, and the 'counterfactual test' can be used to determine whether he desires the effect in acting. In my version, the DDE has its rationale in virtue ethics; it is not liable to abuse as the traditional version is; and it makes more plausible distinctions when applied to standard examples.
Keywords: Virtue Ethics; Responsibility; Practical Reasoning; Intention; double effect; Desire; agent evaluation